2018
DOI: 10.1111/bjd.16705
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab shows high efficacy irrespective ofHLA-Cw6status in patients with moderate-to-severe plaque-type psoriasis: SUPREME study

Abstract: Determination of HLA-Cw6 status for secukinumab therapy is unnecessary, as it is highly effective regardless of HLA-Cw6 status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 37 publications
(44 reference statements)
2
50
0
Order By: Relevance
“…18,19,27 Interestingly, a link between the use of biological drugs such as secukinumab and higher educational attainment was found in our analysis, as also described by Naldi et al 19 In addition, secukinumab has also been suggested in patients with moderate-to-severe psoriasis when a fast response is needed. 28 Overall, the association among patient characteristics, comorbidities and treatment options emerging from our analysis was mostly in-line with published expert opinion on the choice of therapies. For example, a recent publication has recommended ustekinumab and secukinumab as preferred agents for psoriasis patients with obesity, 29 which is also represented by our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…18,19,27 Interestingly, a link between the use of biological drugs such as secukinumab and higher educational attainment was found in our analysis, as also described by Naldi et al 19 In addition, secukinumab has also been suggested in patients with moderate-to-severe psoriasis when a fast response is needed. 28 Overall, the association among patient characteristics, comorbidities and treatment options emerging from our analysis was mostly in-line with published expert opinion on the choice of therapies. For example, a recent publication has recommended ustekinumab and secukinumab as preferred agents for psoriasis patients with obesity, 29 which is also represented by our study.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, secukinumab has also been suggested in patients with moderate‐to‐severe psoriasis when a fast response is needed …”
Section: Discussionmentioning
confidence: 99%
“…Costanzo et al . reported that a similar PASI 90 response was achieved irrespective of HLA‐Cw6 status at week 16, and mean PASI was also comparable at weeks 16 and 24 …”
Section: Systemic Treatmentmentioning
confidence: 76%
“…With the advent of new therapeutic modalities for psoriasis and the introduction of biological therapy for the treatment of psoriasis, several newly published studies showed that there is no association between HLA-Cw06 genetic status and response to treatment especially ustekinumab and Secukinumab. 22 , 23 Other study showed that the presence of HLA-A Bw4-80I could result in reduction in the response to treatment with Etanercept. 24 So HLA alleles play an important role in psoriasis pathogenesis with controversial role in response to biological therapy.…”
Section: Discussionmentioning
confidence: 99%